ANALISIS HUKUM FIQIH DAN HUKUM POSITIF TERHADAP PRAKTIK TALAK DI LUAR PENGADILAN - Wahyu Fitrianoor; Annisa Azzahra; Khulda Azizah (MAQASHIDUNA: Jurnal Hukum Keluarga Islam, 2026)
Abstract This study aims to analyze the validity and legal status of divorce (?al?q) conducted outside the court from the perspective of Islamic jurisprudence (fiqh) and Indonesian positive law. The research employs a qualitative normative approach, by examining statutory provisions, Islamic legal literature, and interviews with officials of the Religious Court. The findings indicate that, according to fiqh law, a divorce pronounced consciously by the husband with explicit wording is considered religiously valid, even without witnesses or official documentation. However, under Indonesian positive law, such a divorce has no legal validity, as it must be conducted before the Religious Court, in accordance with Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). The practice of out-of-court divorce creates legal uncertainty regarding the status of wives and children and may lead to the violation of women?s rights. Therefore, this study emphasizes the necessity of conducting divorce through judicial procedures to ensure legal certainty and protection for both parties.